A clinical study of new onset seizures in children aged 3-12 years - Dwivedi, Rinu; Sudha Priya, P.; Padmavathi, P. (International Journal of Contemporary Pediatrics, 2019)
Background: Seizures are common in pediatric age group and less than 1/3rd of seizures in children are caused by epilepsy. Aim of present study was to analyze the etiological factors and clinical profile of new onset seizures in children aged 3-12 years. Methods: This was a prospective study done at a tertiary care center of south India. Authors analyzed 98 children aged 3-12 years presenting with new onset seizures. Proper history and investigations including EEG, and CT brain were done to confirm the etiology. Results: Out of 98 children 51 were 3-5 yrs of age and 47 were 6-12 years. 66.3% had generalized seizure and 33.6% had partial seizure. Partial seizure were more common in 5-12 years of age. Intracranial infections were the leading cause (73/98) which included neurotuberculosis (26/73), NCC (20), bacterial meningitis (12), cerebral malaria (8) and viral encephalitis (7). Intracranial infections were the leading cause in both age groups. Space occupying lesions were more common in 6-12 years (46.8%) as compared to 3-5 years (19.6%). NCC and Tuberculoma were the leading CT findings in both age groups. There was significantly high incidence of focal EEG changes in partial seizure group compared to generalized seizure group. Conclusions: Intracranial infections were leading cause of new onset seizures especially GTCS. Good clinical evaluation and judicious use of investigations should be ensured. CT brain and EEG are more likely to be informative in partial seizures than in generalized seizures.